Authentic Voices of South Asia - Usman Khalid; KHALID (Usman) (London London Institute of South Asia, 2005)
South Asia is the only large region of the world with unsettled frontiers. It is not because there are is no principles or agreements in existence to resolve disputes and underpin stability, it is because the largest country in the region - India - just does not honour its promises to its people or its agreements with its neighbours. This book is an account of broken promises and the wars and mayhem that they have caused. The irony is that in the case of India the voice of its victims is so thoroughly suppressed or ignored that it appears the victims are the one to blame. This is perhaps the first book where the victims speak out and make their case. It is very different to the hundreds of books that are churned out by India and its friends to blame the dead for being murdered, the women for their rape, the youth for being for being young - 'potential mililtants' taken by the soldiers from their homes and killed in fake encounters. Every one has heard of insurrection in Kashmir and Punjab (Khalistan) and the humiliation of apartheid and Untouchability that its native peoples of India suffer because of the Hindu 'caste system' but very few know how the real truth. This is a 'must read' book for any one wanting to see the true face of India. The chapters of this book are written by the top leader of Kashmir, and of the Sikh and Dalit (Untouchables) struggling for freedom and by scholars/soldiers of Pakistan, Kashmir and Khalistan - the victims of India's imperial ambitions and the subversion and genocide of Sikhs and Muslims that follow. The 'freedom struggle' of Bangladesh is reviewed by as East Pakistani scholar and an Afghan veteran and journalist articulates his proposal to bring peace and stability to Afghanistan.
Keywords: south Asia